2019
DOI: 10.3390/molecules24203708
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Antioxidant, Hypoglycemic Activity, and Identification of Bioactive Compounds in Phenol-Rich Extract from the Marine Red Algae Gracilaria edulis (Gmelin) Silva

Abstract: Obesity and diabetes are major metabolic disorders which are prevalent worldwide. Algae has played an important role in managing these disorders. In this study, Gracilaria edulis, a marine red algae, was investigated for antioxidant and hypoglycemic potential using in vitro models. De-polysaccharide methanol extract of G. edulis was sequentially partitioned with hexane, chloroform, ethyl acetate, and antioxidants, and hypoglycemic potentials were evaluated using multiple methods. High antioxidant potential was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 42 publications
2
15
2
Order By: Relevance
“…DPPH and ABTS radicals were widely used to evaluate the antioxidant ability of polysaccharides. 22,28,29 As shown in Fig. 4A, the scavenging activity of crude polysaccharides DAE-PTXP, As shown in Fig.…”
Section: In Vitro Antioxidant Activity Of Ptxps and Puried Ptxpsmentioning
confidence: 83%
“…DPPH and ABTS radicals were widely used to evaluate the antioxidant ability of polysaccharides. 22,28,29 As shown in Fig. 4A, the scavenging activity of crude polysaccharides DAE-PTXP, As shown in Fig.…”
Section: In Vitro Antioxidant Activity Of Ptxps and Puried Ptxpsmentioning
confidence: 83%
“…The nutritional value of red macroalgae is also due to the diverse content of pigments and antioxidants (14,82,85). Consequently, we determined the total antioxidant capacity (TAC) using a CUPRAC assay (cupric ion reducing antioxidant capacity) that is compatible with lipophilic antioxidants (such as tocopherols) (62) in the oleoresin of A. chilense and in two different botanical lipid extracts, spirulin and maqui, produced with dicloromethane extraction as Gracilex® .…”
Section: Resultsmentioning
confidence: 99%
“…Various methods of extraction are used to obtain enriched fractions derived from seaweeds containing antioxidant and pigment molecules (14, 15), proteins (16), polysaccharides (17) and lipids (18, 19). Particularly in the Gracilaria genus, lipid extractions obtained by classical chloroform:methanol mixtures have revealed a complex lipid composition of glycerolipids and omega-3 and omega-6 polyunsaturated fatty acids and their oxidized derivatives, known as oxylipins (1821).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported that the aqueous extract of N. abor-tristis flowers has the ability to reduce the triglyceride levels in mice blood [21]. The increased uptake of glucose observed with the hexane and ethyl acetate fractions could also lead to a decrease in the differentiation of adipocyte cells [64].…”
Section: Discussionmentioning
confidence: 95%